Implementasi Prinsip Amar Makruf Nahi Munkar Sebagai Etika Politik Islam - Badrul Jihad (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
This article is aimed to discuss the principle of Amar Makruf Nahi Munkar (enjoining what is right and forbidding what is wrong) in relation to Islamic political ethics. This principle is actually one of the main foundations of Islamic teaching that Allah has commanded fellow Muslims to implement. In order to achieve a strong and civilized Muslim society, a principle is needed that holds each individual together in exercising goodness and shunning evil in order to achieve the common good. In this case, Amar Makruf Nahi Munkar is the principle offered by Islam in building such a strong and civilized society.